The elves and the shoemaker - Rosie Greening (Berkhamsted, Hertfordshire Make Believe Ideas, 2017)
A retelling of the story of The elves and the shoemaker in rhyming text Key sound: s-blends spellings: sc, scr, sk, sl, sn, sp, spl, spr, squ, st, str, sw ; Secondary sounds: oi, st (ending) On cover: Includes rhyming activity, key words and picture dictionary